TASK FOR POST-CRISIS IN ROMANIA: THE DEVELOPMENT OF INDUSTRY - Danu, Marcela (Studies and Scientific Researches. Economics Edition, 2013)
The present paper illustrates the role of industry in economic and social development of Romania, in the context of the propagated effects of the contemporary economic and financial crisis and mission that is in the recovery of gaps in relation to EU countries. The dynamic of the industrial sector after 1989, highlighting the continuing decline in its contribution to the GDP formation and changing industry structure in favor of industries producing consumer goods. The situation has changed, however, after the crisis, the industry producing capital goods coming back in force, and hosting the entire sector. Significant is that the development of the Romanian industry must integrate into a viable and sustainable formula, scientific research and technological development with environmental quality. Moreover, the qualitative and quantitative dimensions of industrial development in Romania should be integrated in the dynamic dimensions of the EU, with all the implications and costs derived from this, in the short term. The plea for industrial development in the post-crisis period is supported by the need to ensure a solid foundation for the development of other economic activities specific to the primary and tertiary sectors.